Can the UK achieve the PM. WHO 10 μg m-3 interim target by 2030? - Beevers,S; Kitwiroon,N; Assareh,N; Stewart,G; Dajnak,D (Environmental Health Perspectives, 2022)
Background: The UK Government is currently setting two PM. targets for its Environment Bill. The first is a concentration target to be met by some future date and the second a population exposure reduction target, aimed at reducing exposure gradually over time. Aim: The aim of this research was to combine existing UK 2030 emissions forecasts, the UK’s Climate Change Committee (CCC) Net Zero vehicle forecasts, and the Greater London Authority’s policy forecasts, to establish whether the UK can meet the PM. WHO 10 μg m-3 interim target by 2030, and to assess the likely exposure reduction. Method: We used a combination of European, UK National and London Atmospheric Emissions Inventory forecasts between 2018 and 2030. For road transport we calculated emissions for the Balanced Net Zero Pathway, published by the CCC, which includes widespread vehicle electrification, and two London specific policies aimed at reducing PM.. The emissions were combined with the WRF met. model and the CMAQ-urban coupled model, providing UK PM. concentrations down to 2km spatially and then every 20m close to major roads. Results: UK PM. concentrations in 2030 were below 10 μg m-³, for over 99% of the UK population. In London, the second scenario reduced PM. locally, with <1% of the area of London predicted to be above 10 μg m-3. Accounting for model uncertainty resulted in ~4% of the UK remaining at risk of exceeding 10 μg m-3 albeit in cities such as Birmingham and Manchester. Conclusions: We have shown the combined benefits of UK air quality, Net Zero and local policies for PM. control, in almost achieving the PM. WHO interim target. We identified important but uncertain emissions sources, such as non-exhaust vehicle emissions, cooking aerosol and domestic and industrial wood burning. This work has been submitted to the UK Environment Bill consultation.